Uber : uma análise do perfil do usuário na cidade do Rio de Janeiro - Silva Júnior, Marcelo Dantas da (2018)
Applications (mobile apps) developed to passenger transport vehicles have been utilized in a large scale in cities such as Rio de Janeiro. Taxis and other services such as UBER are the main users of this technology. This paper presents a users´ profile analysis of the mobile apps transport services, with focus on the service provided by the UBER Company. Beginning with the identification of the service users´ profile, the objective of this study is to identify the main reasons for the success of this new transport system. The study also aimed to evaluate if this business model could also be used in similar transport services as conventional taxis. Based on a field survey, we sought to extract information based on demographic, social and motivational aspects to reach the core of the research. Moreover, it was also an objective to find out evidences of the competition between taxis and the service provided by the company. To this end, almost 400 users were interviewed throughout the city of Rio de Janeiro. The results show that UBER users´ profile are different from conventional taxi users – they are predominantly young users, with a high level of education and higher income than the average of Rio population. It was also observed that some respondents were previously public transport users in some daily trips. Moreover, it was possible to identify the new service impact in some regions of the City.